ENHANCING FIFTH GRADERS’ LEARNING INTEREST THROUGH QR CODE-BASED SNAKES AND LADDERS MEDIA - Dya Ayu Agustiana Putri; Leny Suryaning Astutik (SUKMA: Jurnal Pendidikan, 2026)
Learning media through games can increase students’ enthusiasm, as reflected in their learning interest. The purpose of this study was to examine the effect of QR Code-based Snakes and Ladders media on the learning interest of fifth-grade students at SD 2 Tiudan in symbiosis material. Specifically, this research aimed to determine whether the integration of QR Code-based interactive elements into traditional Snakes and Ladders could provide a more engaging and effective learning experience, thereby fostering greater student interest in science learning. This research employed a quantitative approach with an experimental design. The sampling technique used saturated sampling with a total of 60 respondents. Data collection was carried out using a learning interest test. Data analysis employed an independent samples t-test using Jamovi 2.3.28. The post-test t-test results showed a p-value < 0.001, which is lower than 0.05, indicating that H0 was rejected and Ha was accepted. Thus, the QR Code-based Snakes and Ladders media significantly influenced the learning interest of fifth-grade students at SD 2 Tiudan in symbiosis material. Based on the hypothesis testing, it was concluded that QR Code-based Snakes and Ladders media had a significant effect on students’ learning interest in the symbiosis topic.